Adjuvant immunotherapy in patients with resected gastric and oesophagogastric junction cancer following preoperative chemotherapy with high risk for recurrence (ypN+ and/or R1): European Organisation of Research and Treatment of Cancer (EORTC) 1707 VESTIGE study - Lordick, F; Mauer, M E; Stocker, G; Cella, C A; Ben-Aharon, I; Piessen, G; Wyrwicz, L; Al-Haidari, G; Fleitas-Kanonnikoff, T; Boige, V; Lordick Obermannová, R; Martens, U M; et al. (Annals of oncology, 2025)
BACKGROUND: Patients with gastro-oesophageal adenocarcinoma with tumour-positive lymph nodes (ypN+) or positive surgical margins (R1) following neoadjuvant chemotherapy and resection are at high risk of recurrence. Adjuvant nivolumab is effective in oesophageal/oesophagogastric junction cancer and residual pathological disease following chemoradiation and surgery. Immune checkpoint inhibition has shown efficacy in advanced gastro-oesophageal cancer. We hypothesised that nivolumab/ipilimumab would be more effective than adjuvant chemotherapy in high-risk (ypN+ and/or R1) patients with gastro-oesophageal adenocarcinoma following neoadjuvant chemotherapy and resection. PATIENTS AND METHODS: VESTIGE was an academic international, multicentre, open-label, randomised phase II trial evaluating the efficacy of adjuvant nivolumab/ipilimumab versus chemotherapy in gastro-oesophageal adenocarcinoma at high risk of recurrence. Patients were randomised 1 : 1 to receive standard adjuvant chemotherapy (same regimen as neoadjuvant) or nivolumab 3 mg/kg intravenously (i.v.) every 2 weeks plus ipilimumab 1 mg/kg i.v. every 6 weeks for 1 year. Key inclusion criteria included ypN+ and/or R1 status after neoadjuvant chemotherapy plus surgery. The primary endpoint was disease-free survival in the intent-to-treat population. Secondary endpoints included overall survival, locoregional and distant failure rates, and safety according to National Cancer Institute Common Terminology Criteria for Adverse Events v5.0. RESULTS: The independent Data Monitoring Committee reviewed data from 189 of the planned 240 patients in June 2022 and recommended stopping recruitment due to futility. At the time of final analysis, median follow-up was 25.3 months for 195 patients (98 nivolumab/ipilimumab and 97 chemotherapy). Median disease-free survival for the nivolumab/ipilimumab group was 11.4 months [95% confidence interval (CI) 8.4-16.8 months] versus 20.8 months (95% CI 15.0-29.9 months) for the chemotherapy group, hazard ratio 1.55 (95% CI 1.07-2.25, one-sided P = 0.99). The 12-month disease-free survival rates were 47.1% and 64.0%, respectively. There were no toxicity concerns or excess early discontinuations. CONCLUSION: Nivolumab/ipilimumab did not improve disease-free survival compared with chemotherapy in patients with ypN+ and/or R1 gastro-oesophageal adenocarcinoma following neoadjuvant chemotherapy and surgery.
Keywords: dospělí; gastric cancer; Nivolumab; Humans; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; lidé středního věku; lokální recidiva nádoru; Neoadjuvant Therapy; Middle Aged; Esophagogastric Junction; Stomach Neoplasms; chemotherapy; Chemotherapy, Adjuvant; perioperative; nivolumab; mužské pohlaví; oesophagogastric junction cancer; nádory jícnu; Adenocarcinoma; neoadjuvantní terapie; Neoplasm Recurrence, Local; Ipilimumab; Adult; Esophageal Neoplasms; gastroezofageální junkce; immunotherapy; imunoterapie; ženské pohlaví; nádory žaludku; lidé; ipilimumab; adjuvantní chemoterapie; Aged; senioři; Male; adenokarcinom; Immunotherapy; Female